Hubungan Pola Asuh Orang Tua Dengan Kenakalan Remaja Pada Siswa SMK Cokroaminoto Kotamobagu - Firahayu Abas; Sitti Rahma Soleman (Universitas Duta Bangsa Surakarta, 2021)
Introduction: Juvenile delinquency is a negative behavior of young people and social symptoms (pathological) inchildren and adolescents caused by a form of social neglect, so they develop deviant forms of behavior.Objectives: To find out the relationship of parent patterns with adolescent violence in cokroaminoto vocationalschool in kotamobagu.Methods: This study used a descriptive analytic design with a cross-sectional approach with sample 40 students ofclass X and XI SMK Cokroaminoto Kotamoagu. The technique sampling used purposive sampling and analyzed usingchi-square test.Results : From 40 respondents, 26 respondents (65.0%) were not naughty and 14 respondents (35.0%) werenaughty with good parenting 20 respondents (50.0%) and poor parenting 20 respondents (50.0%). Based on theresults of the chi-square test showed both variables with a value <0.003.Conclusions: There is a significant relationship between parenting styles and juvenile delinquency in class x and xistudents of SMK Cokroaminoto Kotamobagu.